MAPPING THE USE OF DIGITAL LEARNING TOOLS AND METHODS FOR INCREASING TEACHERS’ DIGITAL COMPETENCE - Arif, Mohamad Zaenuri; Nurdin, Diding; Sururi, Sururi (JURNAL PENDIDIKAN GLASSER, 2023)
Teachers are required to be able to apply digital tools and media to every aspect of their professional duties. Teachers’ digital competence become important for teachers to acquire. This research purpose is to mapping the use of digital technologies in teachers’ practice. Data was obtained through a survey and analized with descriptive statistics analysis from 93 samples of elementary, middle school, high school, and vocational school teachers. The results show 56.99% teachers use smartphones for learning tools while other 43.01% use PC/laptop device. As many as 48.39% teachers conduct digital learning through message app, 19.35% through LMS, and the rest through online meeting, social media, or all of the type simultaneously. The type of the content dominated by video and image, obtained through web content providers that are searched through search engine. Teachers also use text to give guidance for students, and quiz for formative and summative assessment. A total of 22 teachers carried out asynchronous learning, 35 synchronous learning, and 33 hybrid learning. In conclusion, teachers more often use smartphones, messaging app, and learning media that contain text, with additional video or image content for the learning process, guidance, and quizzes in assessments provided through synchronous and hybrid learning